Primal leadership unleashing the power of emotional intelligence - Goleman, Daniel (Boston Harvard Business School Press, 2013)
This is the book that established ?emotional intelligence? in the business lexicon?and made it a necessary skill for leaders.
Includes bibliographical references and index
Keywords: Leadership -Psychological aspects